Three-dimensional analysis of dental arch forms in Italian population - Bruno Oliva; Simone Sferra; Anna Lucia Greco; Francesco Valente; Cristina Grippaudo (SpringerOpen, 2018)
Abstract Background The aim of this study was the comparison of male and female upper and lower dental arch form in untreated Italian patients by 3D analysis, to find differences in shape, in transversal and longitudinal diameters between sexes, and to give a representative set of population's dental arch to clinicians in order to provide suitable orthodontic treatment. Methods The sample consisted of 3D scans of dental casts deriving from 104 Italian untreated patients (Male = 35, Female = 69) in permanent dentition. An evaluation of the arch form was performed by angular and linear values on every patient using a 3D software (SolidWorks®). A Student's two-tailed t test was used to determine if the differences in measurements between the male and female groups were significant and the level of significance was set at P < 0.05. Results Statistically significant differences in upper and lower transversal and longitudinal diameters were found. Male arch widths were significantly larger than those of females. Male intercanine, intermolar, and interpremolar diameters were significantly greater than females. Dental arch depth was significantly smaller in the female group. Anterior upper dental arch form was flatter, wider, and less sharp in the female group. Conclusions Basing on the anatomical arches differences found between sexes concerning Italian patients, it is suggested to have regard to each patient pre-treatment arch form, width, and depth during orthodontic treatment according to gender.